Conservation and Expression Patterns Divergence of Ascorbic Acid d-mannose/l-galactose Pathway Genes in Brassica rapa - Duan, Weike; Ren, Jun; Li, Yan; Liu, Tongkun; Song, Xiaoming; Chen, Zhongwen; Huang, Zhinan; Hou, Xilin; Li, Ying (Frontiers in Plant Science, 2016)
Ascorbic acid (AsA) participates in diverse biological processes, is regulated by multiple factors and is a potent antioxidant and cellular reductant. The D-mannose/L-galactose pathway is a major plant AsA biosynthetic pathway that is highly connected within biosynthetic networks, and generally conserved across plants. Previous work has shown that, although most genes of this pathway are expressed under standard growth conditions in Brassica rapa, some paralogs of these genes are not. We hypothesize that regulatory evolution in duplicate AsA pathway genes has occurred as an adaptation to environmental stressors, and that gene retention has been influenced by polyploidation events in Brassicas. To test these hypotheses, we explored the conservation of these genes in Brassicas and their expression patterns divergence in B. rapa. Similar retention and a high degree of gene sequence similarity were identified in B. rapa (A genome), Brassica oleracea (C genome) and Brassica napus (AC genome). However, the number of genes that encode the same type of enzymes varied among the three plant species. With the exception of GMP, which has nine genes, there were one to four genes that encoded the other enzymes. Moreover, we found that expression patterns divergence widely exists among these genes. i) VTC2 and VTC5 are paralogous genes, but only VTC5 is influenced by FLC. ii) Under light treatment, PMI1 co-regulates the AsA pool size with other D-Man/L-Gal pathway genes, whereas PMI2 is regulated only by darkness. iii) Under NaCl, Cu2+, MeJA and wounding stresses, most of the paralogs exhibit different expression patterns. Additionally, GME and GPP are the key regulatory enzymes that limit AsA biosynthesis in response to these treatments. In conclusion, our data support that the conservative and divergent expression patterns of D-Man/L-Gal pathway genes not only avoid AsA biosynthesis network instability but also allow B. rapa to better adapt to complex environments.